Creativity. A biological weapon? - Cabeca, Paulo (2021)
We continue in this text the investigation that takes place in Cabeça Paulo (2021) . It is intended in this work to analyze the various definitions that exist for the phenomenon of creativity and to contribute to a reflection on the theme of its definition. Considering that although studied in various areas, from art, to history, from psychology to psychiatry, from zoology to philosophy, from mathematics to neurology, among others, creativity continues today without a concrete definition stripped of ambiguities. Could it be a genetic tool naturally common to many living things? Common to many animal species, which allows them to interact and thrive in the environment, is creativity a biological phenomenon? Is Art, eventually as a manifestation of the subconscious, a consequence of it?